A clinicopathological study of Rhinosporidiosis (Bangladesh Journal of Otorhinolaryngology, 2016)
Introduction: Rhinosporidiosis is one of the common tropical diseases in ENT practice in this subcontinent having the affinity for the mucosa of upper respiratory tract chiefly the nose & nasopharynx. Though this chronic granulomatous disease is quite common in this subcontinent but its distribution is not even.Objectives: The aim of this study is to find out the age distribution, clinical sign-symptoms& attachment of rhinosporidiosis, thats mean to establish the clinical profile of the patient.Method: A cross sectional study was done at the department of ENT & HNS, Sir Salimullah Medical College Mitford Hospital from January to December 2012. The study included 49 patients treated in this department and histologically proved.Rersults: Among 49 patients there was male predominance(37), female were-12. Majority of the patient presented with the feature of nasal obstruction(27), nasal mass(23) and its majority site of attachment was nasal septum(30). In anatomical site distribution majority cases(39) it was distributed in nose & nasopharynx.Conclusion: This study suggests total excision, wide base cauterization and regular follow up to prevent recurrence.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 94-96